Focus on PTEN Regulation - Bermúdez Brito, Miriam; Goulielmaki, Evangelia; Papakonstanti, Evangelia A. (Frontiers in Oncology, 2015)
The role of PTEN as a tumour suppressor has been for a long time attributed to its lipid phosphatase activity against PI(3,4,5)P3, the phospholipid product of the class I PI3Ks. Besides its traditional role as a lipid phosphatase at the plasma membrane, a wealth of data has shown that PTEN can function independently of its phosphatase activity and that PTEN also exists and plays a role in the nucleus, in cytoplasmic organelles and extracellularly. Accumulating evidence has shed light on diverse physiological functions of PTEN which are accompanied by a complex regulation of its expression and activity. PTEN levels and function are regulated transcriptionally, post-transcriptionally and post-translationally. PTEN is also sensitive to regulation by its interacting proteins and its localization. Herein, we summarize the current knowledge on mechanisms that regulate the expression and enzymatic activity of PTEN and its role in human diseases.